2017
DOI: 10.15252/msb.20167490
|View full text |Cite
|
Sign up to set email alerts
|

Integration of over 9,000 mass spectrometry experiments builds a global map of human protein complexes

Abstract: Macromolecular protein complexes carry out many of the essential functions of cells, and many genetic diseases arise from disrupting the functions of such complexes. Currently, there is great interest in defining the complete set of human protein complexes, but recent published maps lack comprehensive coverage. Here, through the synthesis of over 9,000 published mass spectrometry experiments, we present hu.MAP, the most comprehensive and accurate human protein complex map to date, containing > 4,600 total comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
245
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(255 citation statements)
references
References 85 publications
3
245
0
Order By: Relevance
“…In order to test this observation for interacting proteins in general, we collated all large-scale, annotated protein-protein interaction (PPI) datasets generated by individual or joint research groups over the past five years (Drew et al, 2017; Hein et al, 2015; Marsh et al, 2013; Rolland et al, 2014; Thul et al, 2017; Wan et al, 2015), including Core CORUM as the gold-standard literature reference (Ruepp et al, 2010). We again found that gene pairs with an annotated PPI consistently exhibited greater fitness profile correlations across all datasets than gene pairs that did not have an annotated interaction (Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
“…In order to test this observation for interacting proteins in general, we collated all large-scale, annotated protein-protein interaction (PPI) datasets generated by individual or joint research groups over the past five years (Drew et al, 2017; Hein et al, 2015; Marsh et al, 2013; Rolland et al, 2014; Thul et al, 2017; Wan et al, 2015), including Core CORUM as the gold-standard literature reference (Ruepp et al, 2010). We again found that gene pairs with an annotated PPI consistently exhibited greater fitness profile correlations across all datasets than gene pairs that did not have an annotated interaction (Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
“…3,000 co-fractionation / mass spectrometry experiments [4, 6], and restrict direct contact predictions to known co-complex interactions. Specifically, we use complexes with structures in the PDB for evaluation and a set of 896 protein complexes larger than 4 unique subunits derived from >9000 published mass spectrometry proteomics experiments [1, 3, 4, 6] in hu.MAP [32], for all other predictions. In all, we identified 2,434 potential interactions ( S3 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we filtered our reported direct contact predictions by protein interactions that are present in 896 complexes larger than 4 subunits from the human protein complex map, hu.MAP [32]. This step was to ensure pairs of proteins are present in the same complex thereby increasing the likelihood of direct contact.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations